Clinical and parasitological evaluation of dogs naturally infected by Leishmania (Leishmania) chagasi submitted to treatment with meglumine antimoniate and allopurinol - Ikeda-Garcia, Fabiana Augusta [UNESP]; Lopes, Raimundo Souza [UNESP]; Marques, Fábia Judice; Ciarlini, Paulo Cesar [UNESP]; Lima, Valéria Marçal Felix de [UNESP]; Morinishi, Celina Kazue; Zanette, Maurício Franco; Perri, Silvia Helena Venturoli [UNESP]; Marcondes, Mary [UNESP] (My University, 2010)
Aiming to assess the efficacy of the treatment, to verify the occurrence of possible disease relapses and to search for the presence of parasites after the treatment, seven dogs naturally infected by Leishmania sp., were submitted to a treatment with meglumine antimoniate and allopurinol. For this, lymph node and bone marrow aspiration biopsies were carried out at seven moments. After the end of the six-month observation period all dogs were submitted to euthanasia. Then, spleen and liver imprints and in vitro cultures were carried out to search for amastigote forms of the parasite. All animals presented remission of the symptoms and during all the observation period no dog presented relapse of the disease, although amastigote forms of the parasite were observed in two of the animals at the end of the experiment. Thus, it was possible to conclude that the treatment promotes clinical healing but it does not eliminate the parasites completely.
Avaliação clínica e parasitológica de cães naturalmente infectados por Leishmania (Leishmania) chagasi submetidos a tratamento com antimoniato de meglumina e alopurinol
Keywords: Allopurinol; Dogs; Meglumine antimoniate; Treatment; Visceral leishmaniasis; Animalia; Canis familiaris; Leishmania donovani chagasi; Leishmania sp.